Fatal Empyema Thoracis Caused by Nocardia otitidiscaviarum - Gu Q; Zhou L; Shen X; Xu L; Wu G; Pan W; Lin W; Lv D; Lin L; Yan S (Infection and Drug Resistance)
Qianqian Gu,* Lingren Zhou,* Xiaofei Shen, Le Xu, Guixian Wu, Weijia Pan, Wenxia Lin, Dongqing Lv, Ling Lin, Shuangquan Yan Department of Respiratory Medicine, Taizhou Hospital of Zhejiang Province Affiliated to Wenzhou Medical University, Taizhou, 317000, People’s Republic of China*These authors contributed equally to this workCorrespondence: Ling Lin; Shuangquan Yan, Hospital of Zhejiang Province affiliated to Wenzhou Medical University, 150 Ximen Street, Taizhou, 317000, People’s Republic of China, Email Linling@enzemed.com; ysq25908712@163.comAbstract: Nocardiosis caused by Nocardia otitidiscaviarum is exceptionally rare and characterized by a high mortality rate. It typically affects immunocompromised patients, resulting in severe pulmonary or disseminated infections, and is notorious for abscess formation. Empyema resulting from nocardiosis is even less common. Early clinical signs and imaging findings lack specificity, culture growth is sluggish, and the absence of an effective serological detection method can delay treatment. We report an 81-year-old patient with chronic obstructive pulmonary disease treated by long-term inhalation of high-dose salmeterol fluticasone. The initial empirical anti-infection treatment proved ineffective, resulting in rapid disease progression before the confirmation of nocardiosis with empyema through cultures of pleural fluid and sputum. Despite active treatment measures, the patient succumbed to severe pulmonary infection, sepsis, and multiple organ failure. A review of the literature, together with clinical experience, indicates that conventional empirical treatment for Nocardia otitidiscaviarum infection may not always be effective due to the escalating rate of drug resistance. Therefore, the primary step in the management of the infection is timely diagnosis using different methods. Furthermore, the identification of the responsible strain followed by conducting drug sensitivity tests is paramount for the successful treatment of this disease.Keywords: severe nocardia pneumonia, empyema, drug resistance rate, drug sensitivity test